2017
DOI: 10.3892/ol.2017.6936
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Rictor protein in colorectal cancer is correlated with tumor progression and prognosis

Abstract: Abstract. In order to understand the clinical significance of rapamycin-insensitive companion of mammalian target of rapamycin (Rictor) in colorectal cancer (CRC), 62 CRC tissue samples excised during operations were evaluated by immunohistochemistry. Analysis of the association between the expression level of Rictor protein and clinicopathological parameters demonstrated that the expression level of Rictor in CRC tissues was significantly higher than that in paracarcinoma tissues (P<0.0001). In cellular exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…mTOR as part of mTORC2 requires the presence of its partners rictor and SIN1 to function. Rictor has been found to be highly expressed in certain types of cancers, such as colorectal cancer and non-small cell lung cancer [208,290]. Therefore, there has been interest in using rictor as a target for cancer therapeutics.…”
Section: Targeting Mtorc2 Signalingmentioning
confidence: 99%
“…mTOR as part of mTORC2 requires the presence of its partners rictor and SIN1 to function. Rictor has been found to be highly expressed in certain types of cancers, such as colorectal cancer and non-small cell lung cancer [208,290]. Therefore, there has been interest in using rictor as a target for cancer therapeutics.…”
Section: Targeting Mtorc2 Signalingmentioning
confidence: 99%
“…A study on TELO2 in CRC demonstrates that a germline mutation of TELO2 regulated the senescence pathway and is related to sessile serrated adenomas and adenocarcinoma progression ( 15 ). Additionally, rapamycin-insensitive companion of mTOR (RICTOR), a specific adaptor of mTORC2 ( 16 ), plays an important role in cancer cell proliferation, autophagy, migration, and invasion via activation of protein kinase B (Akt) ( 17 , 18 ) and is positively correlated with prognosis in CRC ( 19 ). Thus, we hypothesized that TELO2 is important in the development of CRC via mTOR and RICTOR.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, it has been reported that heterozygous deletion of ATG5 activated EGFR and Wnt/β–catenin pathways in adenomas of Apc(Min/+) mice leading to the enhancement of the IFN γ-dependent inhibition of these pathways [ 43 ]. Moreover, more recent studies have suggested that the controversial role of ATG5 in CRC might be due to the compensatory activation of autophagy-related proteins (AKT, RICTOR and mTOR) in response to autophagy inhibition [ 44 ], which have also been associated with CRC prognosis [ 45 ]. In contrast to the notion of a role of the ATG5 locus in modulating autophagy, our study has suggested that the ATG5 rs546456 SNP might influence CRC risk by modulating host immune responses.…”
Section: Discussionmentioning
confidence: 99%